Petitions - Edwards, Henry Tollemache, 1834-1915.; New South Wales. Parliament. Legislative Assembly (1881)
Petitions: Nos. 1 and 3 to the Legislative Assembly of N.S.W. Parliament, from the residents in the District of Cooma (Monaro electoral district) [No. 1] and from the residents of Bombala, Delegate Cathcart and Bibbenluke (Monaro electoral district) [No. 2].
Manuscript reference no. : NLA MS 2957.
Photocopy of MS.
Petition No. 1 presented by Robert L. Firth; no. 3 by H.S. Badgery. Both request that a railway line be built to Cooma.
Descriptive list (5 p.) available.
Keywords: Railroads -- New South Wales -- Cooma